Factors influencing for choosing of general certificate advanced level [g.c.e (a/l)] stream: a case study of general ordinary level [g.c.e (o/l), (2012)] students in jaffna town, sri lanka - Vinthuja, M.; Thanusha, S.; Vijayananda, C.; Niruthika, K.; Vivitha, J.; Thanarupan, Y. (university of Jaffna, 2014)
Choice of stream is vital for every student future successful career path. Now-a-days students are facing problem when they have to choice the stream. In this view several factors are behinding for the selection of A/L stream. According to the Sri Lankan education system has five streams such as Science, Mathematics, Commerce, Arts and Technology. Out of them, students are compulsory undertaking one. The objective of this study is to determine the factors which influence on choice of A/L stream among O/L students of leading schools in Jaffna town Sri Lanka. The factors are investigated like personal interest, skills & knowledge enhancement, work related concern, parental relations, friends involvement and financial support. The study was conducted by using survey design with a convenience sampling of leadings schools of Jaffna town. The data for this study has been collected by using direct personal interview. The findings of this study revealed that Personal factors are most influencing when choosing of A/L stream among O/L students of leading schools in Jaffna town Sri Lanka. As well as following other factors influencing like family and friends, financial background, school restrictions and job opportunities.
Keywords: Advance level (A/L); Ordinary level (O/L); Stream choice